Genetic characterization based on the D-loop MtDNA and the TSPY genes of the Dwarf Siamang (Hylobates klossii) of Mentawai Island, Indonesia - Rizka Hasanah; UUS SAEPULOH; DYAH PERWITASARI-FARAJALLAH; WALBERTO SINAGA; YOHANA TRI HASTUTI; DONDIN SAJUTHI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hasanah R, Saepuloh U, Perwitasari-Farajallah D, Sinaga W, Hastuti Y, Sajuthi D. 2020. Genetic characterization based on the D-loop MtDNA and the TSPY genes of the Dwarf Siamang (Hylobates klossii) of Mentawai Island, Indonesia. Biodiversitas 21: 2854-2861. Hylobates klossii is an endemic primate on the Mentawai Island, Indonesia that categorized as endangered species due to fragmentation, illegal hunting, and habitat loss. This study aimed to analyze the genetic characterization of H. klossii based on maternal and paternal lineages. The samples were collected from TSI (Bogor, Indonesia) cage consist of two males and two females (blood and fecal of four individuals) and Siberut Island, Mentawai, West Sumatra, Indonesia from one unknown gender (one individual fecal sample). PCR amplification was carried out on DNA and cDNA samples using specific primers for D-loop MtDNA and TSPY genes. The amplicon was analyzed with MEGA-7. The dimensional structure model of the TSPY protein was determined using I-TASSER and visualized with PyMol. The maternal analysis showed five samples consisted of four haplotypes revealed that Nam-nam and April were identic with 0% genetic distance. It’s revealed that Nam-nam and April were mother and son. The paternal analysis of two H. klossii males revealed that April was the closest relative to H. muelleri (99.56% identity) and Gou-gou to H. klossii (100% identity). Characterization of partial TSPY gene (990 bp) of April and Gou-Gou indicated four amino acids mutation, causing the shift in-amino acid structure position. The results assumed that April was a cross-breeding between H. klossii female and H. muelleri male. This genetic characterization is expected to support the conservation efforts through recommendations for good management in H. klossii preservation.